From innovative teacher education to creative pedagogical designs - Kohler, Alaric; Boissonnade, Romain; Giglio, Marcelo (My University, 2015)
This contribution is about the design of innovative teaching practices. Innovation is fostered by a focus on creative tasks for school pupils, and supported by teacher education courses. Two examples of teacher education practice are presented, both requiring from student teachers to produce innovative pedagogical designs. A pedagogical design is defined by a specific set of tasks, by a social setting and by a sequence. The first example requires pedagogical designs offering a thinking space to learners, while the second example is based on an iterative research methodology (PIO). The discussion of these two examples stresses two features of these practices, that can be considered supporting creativity and agency in classroom activities: the anticipation and confrontation between prediction and observation, and the articultion of collective and solitary moments of work in specific sequences. Future research could investigate the potential support the various combinations of collective and solitary moments of activity offer to creativity. These combinations can be designed for teaching practices to fit specific pedagogical and learning objectives, and can be evaluated through micro-design research.
Keywords: creativity collaboration innovation pedagogical design teacher education